Lower class children and the state during World War Two in urban Turkey: streets, schools and worksites - Dilber, Özlem. (Thesis (M.A.)-Bogazici University.Atatürk Institute for Modern Turkish History, 2009., 2009)
The aim of this thesis is to discuss the history of childhood and the state involvement of control on the bodies and minds of children during the Second World War in Turkey by scrutinizing three spaces of children of lower orders; streets, work sites and schools. For that purpose, the nature of social policy applications towards children and the educational policies are elucidated in the war context. The main focus of the thesis is to depict the scopes and ways of control over children in each mentioned space. The research is based on the archival documents of Official gazette, various newspapers and journals published in that era, biographies of people who experienced the war and stories written during the war. This study depicts that during the war years in Turkey, the priorities of the government were redefined on the basis of war preparedness which determined the state’s involvement in the childhood space. To make comparison with the other realms of state involvement and the education, noticeably schools became spaces where state’s influence and ideology was depicted mostly and control and discipline over the bodies and minds of the children was actualized.
Keywords: World War, 1939-1945 -- Children -- Turkey.; Children and war -- Turkey.